Work Engagement pada Petugas Layanan Work Engagement on Service Officer - Della Belinda; Lisa Adziani; Fendy Suhariadi; Rini Sugiarti (Philanthropy: Journal of Psychology, 2021)
Work engagement is still an interesting topic to research until now, because employees are an important aspect to ensure the organization can develop or not. Therefore, the organization start paying more attention to humans as human capital to be managed seriously. Research on work engagement in the public sector has attracted quite a lot of attention. Public service employees have different characteristics from other sector employees, both from work patterns and from the work environment. Several research results show that work engagement is heavily influenced by internal factors, but external factors also have an important role in influencing employee work engagement.